2019
DOI: 10.1155/2019/6320515
|View full text |Cite
|
Sign up to set email alerts
|

Wound Photobiomodulation Treatment Outcomes in Animal Models

Abstract: The possibilities that photobiomodulation has brought on to the medical field are ever expanding and the scope it has reached is infinite. Determining how this relatively new treatment technique can be incorporated into the veterinary medical field is of interest to many medical professionals. In this review, we examine the treatment outcomes of low-level-laser therapy (LLLT) in different animal models to pinpoint any similarities between the studies. A search was conducted to identify LLLT studies using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
6
0
2
Order By: Relevance
“…Considering that the new term "photobiomodulation therapy" is designated as "a form of light therapy…in the visible and infrared spectrum…" [12]; in previously published studies, we analyzed the effects of PBM therapy on wound regeneration processes. Wavelengths in the 600 or 800 nm range with daily laser exposure have been shown to be most beneficial in rodent studies, regardless of health condition or wound type [13]. The optimal therapeutic dose when using laser therapy in an open wound is from 0.5 J/cm 2 to 1 J/cm 2 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the new term "photobiomodulation therapy" is designated as "a form of light therapy…in the visible and infrared spectrum…" [12]; in previously published studies, we analyzed the effects of PBM therapy on wound regeneration processes. Wavelengths in the 600 or 800 nm range with daily laser exposure have been shown to be most beneficial in rodent studies, regardless of health condition or wound type [13]. The optimal therapeutic dose when using laser therapy in an open wound is from 0.5 J/cm 2 to 1 J/cm 2 [14].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and number of PBM therapy sessions vary in the literature from one to several dozen [13]. A review by Ebrahimi et al showed that the frequency of irradiation sessions is 3-8 times [16].…”
Section: Discussionmentioning
confidence: 99%
“…Blue LED light medical devices that use specific wavelengths in the blue range of the visible light spectrum have been extensively analyzed in animal models [ 17 , 23 ], and the efficacy and safety of such devices have been demonstrated. Some authors have recently reported observations of an improved healing process when superficial wounds are treated with blue LED light with wavelengths in the range 410–430 nm, and a study in an animal model indicated that blue light led to a faster healing process in superficial lesions, with fibroblasts and myofibroblasts playing an important role [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The light energy interacts with some endogenous chromophores in the blood and skin, activating the photobiomodulation mechanism and thus stimulating the physiological processes of wound healing. The application of medical devices utilizing blue LED light in animal models has been extensively analyzed [ 17 , 23 ], and has demonstrated their efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Lopez, Brundage 20 (2019), os efeitos antinflamatórios e bioestimuladores da Fotobiomodulação podem ser atribuídos a uma reação fotoquímica na área da ferida. Os autores sugerem que o mecanismo principal seja representado pela absorção dos fótons emitidos pelo Laser por parte dos cromóforos presentes nas mitocôndrias das células que integram o microambiente da lesão, gerando um estímulo para síntese de adenosina trifosfato (ATP), bem como uma redução dos níveis de espécies reativas de oxigênio.…”
Section: Discussionunclassified